Mellom borealisme og orientalisme. Fortellinger og forestillinger om 'de andre' i nordlysturismen - Mathisen, Stein Roar (Novus forlag, 2017)
Source at http://ojs.novus.no/index.php/TFK/article/view/1379 . The article takes as its point of departure a media narrative, relating that Northern Lights tourists from the East are not only visiting the northern areas to experience the celestial phenomenon, as their actual hope is to conceive under the Lights. According to alleged old beliefs in the East, this is supposed to give handsomer, healthier, and more intelligent children. The location of these beliefs in the touristic border zone, and relating it to modern tourism imaginaries and myths, opens new perspectives for the understanding of these narratives. Discussing one possible mediated background for what eventually turns into a migratory legend answers some questions. However, the further development and metamorphosis of the legend, and finally its materializations in the tourism industry opens new perspectives on narrated relations between hosts and guests.